Design Choices in Privatized Social-Security Systems: Learning from the Swedish Experience - Cronqvist, Henrik; Thaler, Richard H (American Economic Review, 2004)
Design Choices in Privatized Social-Security Systems: Learning from the Swedish Experience by Henrik Cronqvist and Richard H. Thaler. Published in volume 94, issue 2, pages 424-428 of American Economic Review, May 2004